Tax non-compliance of small-and medium-sized corporations (SMCs) and tax auditors' aggressiveness in judgment when auditing SMCs / Nor Azrina Mohd Yusof @ Ghani - Mohd Yusof @ Ghani, Nor Azrina (2016)
The pervasiveness of tax non-compliance remains a serious concern to most tax authorities around the world. The loss of tax revenue due to tax non-compliance has prompted tax authorities to strengthen their tax audit and tax investigation. In Malaysia, although tax authorities have initiated tax audit regularly and impose tax penalties, the issue of tax non-compliance among small-and medium-sized corporations (SMCs) still persist. The unresolved issue signals the question as to whether the increase in tax noncompliance is due to the tax auditors' aggressiveness in judgment when auditing SMCs. The importance of understanding tax non-compliance as well as tax auditors' aggressiveness in judgment, couple with the lack of empirical research is the motivation of this study. The first objective is to examine the determinants of tax non-compliance of SMCs. This study analysed archival tax data obtained from the Corporate Tax Department, IRBM, located at Duta Street, Kuala Lumpur. A total of 513 audited and resolved corporate tax cases in 2011 were obtained. Of these 513 tax cases, 286 are noncompliant SMCs. The findings show RM31.3 million additional taxes and penalties were collected from these non-compliant SMCs. The hierarchical multiple regression was used to test the proposed research model, which is formulated based on the economic deterrence theory. Out of six hypotheses, four hypotheses are supported whereby tax rate, foreign ownership, firm size and construction industry are found significantly related to tax non-compliance of SMCs. The most significant predictor is firm size followed by construction industry, tax rate and foreign ownership. The second objective is to test the tax auditors' aggressiveness in judgment model based on culpability theory. A total of 357 questionnaires were mailed to tax auditors. Of these, 318 usable questionnaires were received and analysed. There are two important findings from this survey. Firstly, tax auditors indicate that the use of unqualified tax agents, types of industry and firm size cause tax non-compliance among SMCs. These findings are consistent with the findings obtained in Stage 1 where firm size and types of industry are two significant determinants of tax non-compliance. Partial Least Squares-Structural Equation Modelling (PLS-SEM) was used to test the proposed tax auditors' aggressiveness in judgment model. The results show that the culpability factor, job stress and partially task input factors (incompleteness of documentation) exerted significant effects on tax auditors' aggressiveness in judgment. The results also reveal that incompleteness of documentation significantly moderates the relationship between the culpability factor and tax auditors' aggressiveness in judgment, thus answering the third objective. When the degree of incompleteness of documentation is high, the culpability factor (e.g., size of audit adjustment and the number of years involved in tax non-compliance) will have greater influence on the aggressiveness of tax auditors' judgment when auditing SMCs. Overall, this study has merits as it used the actual tax audit cases in measuring tax non-compliance among SMCs in Malaysia. This study contributes to the tax compliance literature by testing the applicability of the economic deterrence theory and the culpability theory in the context of Malaysian tax setting. The findings provide important insights not only to the Malaysian tax authorities, but also to tax authorities and tax researchers in other parts of the world given the fact that tax non-compliance of SMCs is a prevalent and universal problem.